2018
DOI: 10.1002/jcb.26464
|View full text |Cite
|
Sign up to set email alerts
|

MALAT1 modulates the autophagy of retinoblastoma cell through miR‐124‐mediated stx17 regulation

Abstract: The retinoblastoma is the most common intraocular malignant tumor in infants and children; it is one of the deadliest forms of cancer due to its limited sensitivity to chemotherapy and radiotherapy. In several cancers, chemoresistance is associated with autophagy induction. Non-coding RNAs, including long non-coding RNAs (lncRNA) and microRNAs (miRNAs) have been reported to regulate physiological activities of the cells, including proliferation, apoptosis, migration, as well as autophagy. MALAT1, a well-establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 46 publications
3
46
0
Order By: Relevance
“…36,37 Moreover, lncRNAs seemed to penetrate into all aspects of gene regulation, including epigenetic inheritance, transcription, post-transcription and translation. 38,39 Interestingly, Jun Huang et al 40 reported that lncRNA MALAT1 mediated autophagy of retinoblastoma cells through acting on miR-124. Alternatively, lncRNA H19 inhibited progression of retinoblastoma cells via offsetting the action of miR-17-92 cluster, 41 and lncRNA CCAT1 negatively regulated miR-218-5p to facilitate the proliferation and growth of SO-RB50 and Y79 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Moreover, lncRNAs seemed to penetrate into all aspects of gene regulation, including epigenetic inheritance, transcription, post-transcription and translation. 38,39 Interestingly, Jun Huang et al 40 reported that lncRNA MALAT1 mediated autophagy of retinoblastoma cells through acting on miR-124. Alternatively, lncRNA H19 inhibited progression of retinoblastoma cells via offsetting the action of miR-17-92 cluster, 41 and lncRNA CCAT1 negatively regulated miR-218-5p to facilitate the proliferation and growth of SO-RB50 and Y79 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis associated lung adenocarcinoma transcript 1 (MALAT‐1) interacts with SR proteins and is located on nuclear speckles close to the spliceosome machinery (Tripathi et al, ; Wilusz, ). Downregulation of lncRNA MALAT‐1 is related to reduced cell proliferation in vitro (J. Huang, Yang, Fang, & Liu, ). In ovarian cancer, it associates with regulatory splice protein RNA‐binding protein fox‐1 homolg 2 (RBFOX2).…”
Section: Splicing Alterations In Cancermentioning
confidence: 99%
“…Researchers found lncRNA‐MALAT1 was robustly induced by hypoxia in several cancer cell types . In addition, several studies reported that lncRNA‐MALAT1 modulates the activity of autophagy . More importantly, recent research indicated expression of lncRNA‐MALAT1 was significantly increased in the ectopic endometrium of patients with ovarian endometriosis .…”
Section: Introductionmentioning
confidence: 99%